2017
DOI: 10.1039/c7ra05621d
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide B lowers body weight and ameliorates hepatic steatosis in high-fat diet-induced obese mice correlated with pregnane X receptor activation

Abstract: Ginkgolide B (GB) is a natural occurring terpene lactone and a selective agonistic ligand of hPXR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 37 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…F I G U R E 5 Forest plot of Ginkgo biloba effect on tumor necrosis factor-α level, (pg/ml), WMD; weighted mean difference On the other hand, the insulin signaling cascade was significantly stimulated by the over-expression of lipid receptor R1 (Adipo R1), insulin receptor, IL-10, and protein kinase B (Akt) phosphorylation (Hirata et al, 2015). Furthermore, ginkgolide B decreased levels of serum TG and body weight, and improved hepatic steatosis in diet-induced obesity in mouse liver via overexpression of pregnane X receptor (PXR) genes (Luo et al, 2017). One animal study on streptozotocin-induced diabetes assessed the effects of three doses of GBE (50, 100, and 200 mg/kg) on renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…F I G U R E 5 Forest plot of Ginkgo biloba effect on tumor necrosis factor-α level, (pg/ml), WMD; weighted mean difference On the other hand, the insulin signaling cascade was significantly stimulated by the over-expression of lipid receptor R1 (Adipo R1), insulin receptor, IL-10, and protein kinase B (Akt) phosphorylation (Hirata et al, 2015). Furthermore, ginkgolide B decreased levels of serum TG and body weight, and improved hepatic steatosis in diet-induced obesity in mouse liver via overexpression of pregnane X receptor (PXR) genes (Luo et al, 2017). One animal study on streptozotocin-induced diabetes assessed the effects of three doses of GBE (50, 100, and 200 mg/kg) on renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…During the research, a positive, antiatherogenic, anti-obesity and anti-diabetic effect of ginkgo on the metabolism of mammalian organisms was observed. The effects of both leaf extracts [ 130 , 139 , 162 , 163 , 164 ] and seeds [ 165 ], vinegar obtained from fermenting seeds [ 166 ], leaves [ 148 , 167 ], well as ginkgolide B [ 123 , 168 ] and ginkgolide C [ 169 ] were investigated. During the research, positive changes in body weight (decrease) were observed [ 163 , 164 , 170 ], and a reduction in adipose tissue mass [ 167 , 168 , 169 ] was caused by the reduction of fat cells (adipocytes) [ 169 , 170 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…The effects of both leaf extracts [ 130 , 139 , 162 , 163 , 164 ] and seeds [ 165 ], vinegar obtained from fermenting seeds [ 166 ], leaves [ 148 , 167 ], well as ginkgolide B [ 123 , 168 ] and ginkgolide C [ 169 ] were investigated. During the research, positive changes in body weight (decrease) were observed [ 163 , 164 , 170 ], and a reduction in adipose tissue mass [ 167 , 168 , 169 ] was caused by the reduction of fat cells (adipocytes) [ 169 , 170 ]. Blood tests showed positive changes in the fat profile [ 145 , 164 ], including lowering cholesterol and triglycerides [ 167 , 168 ], and the regulation of lipid metabolism, glucose and insulin [ 166 , 167 ] had a positive effect on the condition and functioning of the kidneys [ 130 ].…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
“…e impacts of ginkgolide B on hepatic steatosis and body weight were studied in a high-fat diet-induced model of obesity in C57BL/6 male mice, which revealed that treatment with ginkgolide B (0.1% per day) induced human pregnane X receptor (hPXR) mRNA expression in the liver in a dose-dependent manner, without affecting the expression of peroxisome proliferatoractivated receptor (PPAR), liver X receptor (LXR), farnesyl X receptor (FXR), or LXR trans-activities. Ginkgolide B also reduced plasma triglyceride (TG) levels and body weights while resolving hepatic steatosis [80]. Treatment with 3-100 M ginkgolide C substantially decreased lipid aggregation in an in vitro study of HepG2 liver cells and increased TG degradation by increasing the phosphorylation of hormone-sensitive lipase and the production of adipose TG lipase.…”
Section: Antiobesity Effectsmentioning
confidence: 99%